Assessment of Alternaria Toxins and Pesticides in Organic and Conventional Tomato Products: Insights into Contamination Patterns and Food Safety Implications - Tommaso Pacini; Teresa D’Amore; Stefano Sdogati; Emanuela Verdini; Rita Bibi; Angela Caporali; Elisa Cristofani; Carmen Maresca; Serenella Orsini; Alessandro Pelliccia; Eleonora Scoccia; Ivan Pecorelli (Toxins)
Alternaria toxins (ATs) are a group of toxins produced by Alternaria fungi that frequently contaminate tomatoes and tomato products. Recently, the European Food Safety Authority evaluated ATs for their genotoxic and carcinogenic properties. Alternaria infestation is often controlled using ad hoc treatment strategies (fungicides). In this study, two analytical methods were developed, validated and applied for the determination of five ATs and 195 pesticides in tomato products collected from the Italian market. Two distinct groups, organic (n = 20) and conventional (n = 20) Italian tomato sauces, were characterized in depth. Tenuazonic acid, alternariol and alternariol monomethyl ether were found up to 517, 27 and 7.1 µg/kg, respectively, while pesticides were detected between 0.0026 and 0.0421 mg/kg in conventional products, and, interestingly, up to 0.0130 mg/kg in organic products. No correlation emerged between the detected levels of ATs and pesticides and the type of tomato cultivation, but the probability of pesticide contamination in conventional products was eight times higher than in organics. Some considerations about exposure assessment and risk characterization for ATs were also proposed in the overall population and in more sensitive and/or exposed subgroups, underlining the need for new focused toxicological and monitoring studies to establish reliable reference values. Moreover, these data highlight that fungicide treatments may not protect tomatoes from ATs contamination, although it may remove fungi infestation. As organic product consumption is increasing, it is important to lay down dedicated regulations for maximum permitted levels to ensure the food safety of these products that are often perceived by consumers as a healthier and environmentally friendlier choice.